Organization of GABAergic synaptic circuits in the rat ventral tegmental area. - Alessandro Ciccarelli; Arianna Calza; Patrizia Panzanelli; Alessandra Concas; Maurizio Giustetto; Marco Sassoè-Pognetto (PLoS ONE)
The ventral tegmental area (VTA) is widely implicated in drug addiction and other psychiatric disorders. This brain region is densely populated by dopaminergic (DA) neurons and also contains a sparse population of γ-aminobutyric acid (GABA)ergic cells that regulate the activity of the principal neurons. Therefore, an in-depth knowledge of the organization of VTA GABAergic circuits and of the plasticity induced by drug consumption is essential for understanding the mechanisms by which drugs induce stable changes in brain reward circuits. Using immunohistochemistry, we provide a detailed description of the localization of major GABA(A) and GABA(B) receptor subunits in the rat VTA. We show that DA and GABAergic cells express both GABA(A) and GABA(B) receptors. However VTA neurons differ considerably in the expression of GABA(A) receptor subunits, as the α1 subunit is associated predominantly with non-DA cells, whereas the α3 subunit is present at low levels in both types of VTA neurons. Using an unbiased stereological method, we then demonstrate that α1-positive elements represent only a fraction of non-DA neurons and that the ratio of DA and non-DA cells is quite variable throughout the rostro-caudal extent of the VTA. Interestingly, DA and non-DA cells receive a similar density of perisomatic synapses, whereas axo-dendritic synapses are significantly more abundant in non-DA cells, indicating that local interneurons receive prominent GABAergic inhibition. These findings reveal a differential expression of GABA receptor subtypes in the two major categories of VTA neurons and provide an anatomical basis for interpreting the plasticity of inhibitory circuits induced by drug exposure.